Pengeluaran Pemerintah Untuk Pembangunan Daerah - Irfan Hamdani; Nugia Sri Nesta; Junita Rahmawati; Faisal Hidayat (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Government expenditure is a component of fiscal policy, which is the action taken by the government to control how the economy develops by deciding how much money will be available for spending and revenue each year, as stated in the Budget revenue document. State Budget and Expenditures (APBN). In accordance with the unitary principle that regional government cannot be separated from the central government, on that basis, the independence of a region in managing its household affairs does not mean that each regional government must be able to finance all expenditures with its own Regional Original Revenue (PAD). This budget strategy aims to stabilize production levels, job prospects, and prices while encouraging economic expansion. Government expenditure and GRDP, or economic growth, are closely related because development spending is meant to support the role of development agencies and will result in the production of goods that are essential for advancing economic progress. The APBD, which includes income, expenditure and expenditure financing at the provincial/regional/city level, reflects regional government spending. Spending by the government has grown in tandem with tax revenues. For direct government expenditure display and exposure, expenditures directly related to programs or activities are bundled together as technical newspaper expenditures, while other expenditures are not. The regional revenue and expenditure budget, which includes revenue, spending and financing, reflects regional government expenditure at the provincial/district/city level. The difference between financing expenditures and expenditures is that financing expenditures involve spending money from the regional general treasury which will eventually be reimbursed, whereas expenditures involve spending money from the state/regional general treasury which will not be replaced.